Analisis Dakwah Ust. Abdul Somad Di Youtube Terhadap Sosial Positif Bagi Masyarakat - Anggun Anugrah; Khairuddin (Al-Manaj : Jurnal Program Studi Manajemen Dakwah, 2026)
This study examines contemporary Islamic preaching media by Ustadz Abdul Somad on YouTube regarding social influence, as well as Islamic preaching messages through social media that impact the behavior and social values ​​of society. Through a qualitative approach with a descriptive approach, secondary data is seen from uploaded content and collecting information and literature studies, primary data is screenshot documentation evidence. This study aims to analyze Islamic preaching communication and Islamic preaching media. The results of this study using communication and media theory, Islamic preaching on YouTube platform has proven successful in attracting interest and conveying religious messages. The video entitled "What we prepare is not for sakaratul maut" received the highest number of views with 70% of comments being positive while the video on the law of dating in Islam showed the highest level of engagement with 67% of positive comments. The response from the audience, which is mostly positive, reflects the impact of Islamic preaching on motivation, behavior, and social values ​​in society. These findings indicate that YouTube functions as a significant digital preaching medium and has a broad impact.